Development of automated brightfield double In Situ hybridization (BDISH) application for HER2 gene and chromosome 17 centromere (CEN 17) for breast carcinomas and an assay performance comparison to manual dual color HER2 fluorescence In Situ hybridization (FISH) - Wang Lin; Dietel Manfred; Kurosumi Masafumi; Penault-Llorca Frederique; Walk Eric; Farrell Michael; Gaire Fabien; Murillo Adrian E; Lehrkamp Megan; Hauss-Wegrzyniak Beatrice; Nitta Hiroaki; Loftus Margaret; et al. (BMC, 2008)
Abstract Background Human epidermal growth factor receptor 2 (HER2) fluorescence in situ hybridization (FISH) is a quantitative assay for selecting breast cancer patients for trastuzumab therapy. However, current HER2 FISH procedures are labor intensive, manual methods that require skilled technologists and specialized fluorescence microscopy. Furthermore, FISH slides cannot be archived for long term storage and review. Our objective was to develop an automated brightfield double in situ hybridization (BDISH) application for HER2 gene and chromosome 17 centromere (CEN 17) and test the assay performance with dual color HER2 FISH evaluated breast carcinomas. Methods The BDISH assay was developed with the nick translated dinitrophenyl (DNP)-labeled HER2 DNA probe and DNP-labeled CEN 17 oligoprobe on the Ventana BenchMark® XT slide processing system. Detection of HER2 and CEN 17 signals was accomplished with the silver acetate, hydroquinone, and H2O2 reaction with horseradish peroxidase (HRP) and the fast red and naphthol phosphate reaction with alkaline phosphatise (AP), respectively. The BDISH specificity was optimized with formalin-fixed, paraffin-embedded xenograft tumors, MCF7 (non-amplified HER2 gene) and BT-474 (amplified HER2 gene). Then, the BDISH performance was evaluated with 94 routinely processed breast cancer tissues. Interpretation of HER2 and CEN 17 BDISH slides was conducted by 4 observers using a conventional brightfield microscope without oil immersion objectives. Results Sequential hybridization and signal detection for HER2 and CEN 17 ISH demonstrated both DNA targets in the same cells. HER2 signals were visualized as discrete black metallic silver dots while CEN 17 signals were detected as slightly larger red dots. Our study demonstrated a high consensus concordance between HER2 FISH and BDISH results of clinical breast carcinoma cases based on the historical scoring method (98.9%, Simple Kappa = 0.9736, 95% CI = 0.9222 - 1.0000) and the ASCO/CAP scoring method with the FISH equivocal cases (95.7%, Simple Kappa = 0.8993%, 95% CI = 0.8068 - 0.9919) and without the FISH equivocal cases (100%, Simple Kappa = 1.0000%, 95% CI = 1.0000 - 1.0000). Conclusion Automated BDISH applications for HER2 and CEN 17 targets were successfully developed and it might be able to replace manual two-color HER2 FISH methods. The application also has the potential to be used for other gene targets. The use of BDISH technology allows the simultaneous analyses of two DNA targets within the context of tissue morphological observation.